Pengembangan dan Edukasi Filter Air : Upaya Peningkatan Akses Air Bersih di Desa Baliloku, Wanokaka, Sumba Barat - Alexandro Devara Halim; Irene Angelina (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The issue of clean water supply has become a serious problem in Baliloku Village, Wanokaka, West Sumba. Water quality has been continuously declining each year due to the El Niño phenomenon. Bore wells serve as one of the water sources for the residents of Baliloku Village. However, the substandard water quality forces residents to fetch water from the river, which contains lime and mud, without undergoing any treatment. One of the water treatment methods that can be applied by residents is the use of water filters. This activity aims to help provide clean water suitable for daily activities through the construction of a water filter tower in Baliloku Village. This research is beneficial in improving water quality by reducing the particles contained in lime and muddy water. The construction of this filter utilizes filter sand and activated carbon. The community service method applied is participant observation, which involves direct participation in building the water filter tower in Baliloku Village. The results of this activity indicate a positive change among the residents of Baliloku Village, as they have started using clean water for their daily activities and are capable of maintaining the water filter according to the provided guidelines.